A NUMERICAL STUDY ON HEATING PERFORMANCE OF HORIZONTAL AND VERTICAL EARTH-AIR HEAT EXCHANGERS WITH EQUAL PIPE LENGTHS - Tasdelen, Fatih; Dagtekin, Ihsan (Vinca Inst Nuclear Sci, 2022)
In this study, heating performances of horizontal and vertical earth-air heat exchangers with equal pipe lengths were evaluated in ANSYS FLUENT 19.2 simulation program based on CFD for the winter period of Bitlis, Turkey. Thermal performance analyses regarding vertical and horizontal 3-D-modeled earth-air heat exchangers were evaluated in steady-state condition of the simulation program for different values of Re = 5.10(3), 10(4), 2.10(4), 4.10(4), 6.10(4), 8.10(4), and 10(5) numbers by using standard k-epsilon turbulence model. Numerical results obtained from CFD based simulation program were compared with a numerical study in the literature, and it was determined that there was a consistency between the results. The pressure loss and fan power values of horizontal and vertical earth-air heat exchangers were also investigated in addition their thermal performances. A good agreement was found between the pressure loss values obtained from the theoretical and simulation calculations of both earth-air heat exchangers. Considering the temperature increases in both earth-air heat exchangers, the highest and lowest temperature increases were observed in vertical earth-air heat exchanger with 22.52 K and 10.67 K, respectively. The best thermal performance was observed in vertical earth-air heat exchanger for 5.10(3), 10(4), and 2.10(4) values of Reynolds number and in horizontal earth-air heat exchanger for 4.10(4), 6.10(4), 8.10(4), and 10(5) values of Reynolds number.
Keywords: earth-air heat exchanger; CFD; temperature; Reynolds number; earth; thermal performance